2022
DOI: 10.1186/s42506-022-00106-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of severe acute respiratory syndrome coronavirus 2 spike antibodies in some healthcare settings in Egypt

Abstract: Background Healthcare workers (HCWs) are at the front line in battling infection transmission, such as that in coronavirus disease 19 (COVID-19). Additionally, they may act as potential carriers passing the virus on to others. Anti-spike (anti-S) antibodies for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are formed either as a result of infection or vaccination with both indicating immunity against future COVID-19 infection. Aim Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Zabarsky et al found that 25% of HCWs testing positive for SARS-CoV-2 had a higher risk of exposure at work, as opposed to 14% of infected HCWs who reported higher-risk exposures to family members or other infected individuals in the community (Zabarsky et al, 2021). Other communityrelated behaviors might also influence the risk of COVID-19 infection among HCWs, and these factors were analyzed by the authors elsewhere (El-Ghitany et al, 2022a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zabarsky et al found that 25% of HCWs testing positive for SARS-CoV-2 had a higher risk of exposure at work, as opposed to 14% of infected HCWs who reported higher-risk exposures to family members or other infected individuals in the community (Zabarsky et al, 2021). Other communityrelated behaviors might also influence the risk of COVID-19 infection among HCWs, and these factors were analyzed by the authors elsewhere (El-Ghitany et al, 2022a).…”
Section: Discussionmentioning
confidence: 99%
“…This study was a part of a larger survey that was conducted originally for the purpose of determining COVID-19 seroprevalence in the Egyptian community and among HCWs and the relevant determinants of infection. Details of sampling of HCWs are described elsewhere by the authors (El-Ghitany et al, 2022b). Briefly, a total of 39 hospitals from five governorates were selected using the multistage cluster sampling technique.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an Egyptian study among HCWs reported a much higher rate of asymptomatic cases, where anti-S seropositivity was found in 39.1% of unvaccinated participants. This might be due to their higher exposure to COVID-19 infection [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…This period coincided with the second and third waves of the COVID-19 pandemic in Egypt. This study was a part of another project which enrolled 559 HCWs (10).…”
Section: Methodsmentioning
confidence: 99%